2022
DOI: 10.3390/pharmaceutics14030474
|View full text |Cite
|
Sign up to set email alerts
|

Sustained and Long-Term Release of Doxorubicin from PLGA Nanoparticles for Eliciting Anti-Tumor Immune Responses

Abstract: Immunogenic cell death (ICD) is a powerful trigger eliciting strong immune responses against tumors. However, traditional chemoimmunotherapy (CIT) does not last long enough to induce sufficient ICD, and also does not guarantee the safety of chemotherapeutics. To overcome the disadvantages of the conventional approach, we used doxorubicin (DOX) as an ICD inducer, and poly(lactic-co-glycolic acid) (PLGA)-based nanomedicine platform for controlled release of DOX. The diameter of 138.7 nm of DOX-loaded PLGA nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Moreover, concentrated drug targeting possibly prolongs drug occupancy in pulmonary receptors, thus increasing the effective drug dosage and minimizing adverse side effects [ 21 , 24 , 25 ]. Nowadays, nanocarriers have attracted attention as delivery vectors to protect the drug from early discharge, aid cellular uptake, and boost maximum drug absorption with negligible toxicity [ 26 , 27 , 28 ]. Moreover, the lipid excipient accessibilities within safety standards and capabilities of nanocarriers to enhance hydrophobic drug solubility, long-term stability, ease of production, and deep-lung deposition capacity have revolutionized lipid-based systems, specifically nanoemulsions, as promising drug carrier systems for pulmonary delivery applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, concentrated drug targeting possibly prolongs drug occupancy in pulmonary receptors, thus increasing the effective drug dosage and minimizing adverse side effects [ 21 , 24 , 25 ]. Nowadays, nanocarriers have attracted attention as delivery vectors to protect the drug from early discharge, aid cellular uptake, and boost maximum drug absorption with negligible toxicity [ 26 , 27 , 28 ]. Moreover, the lipid excipient accessibilities within safety standards and capabilities of nanocarriers to enhance hydrophobic drug solubility, long-term stability, ease of production, and deep-lung deposition capacity have revolutionized lipid-based systems, specifically nanoemulsions, as promising drug carrier systems for pulmonary delivery applications.…”
Section: Introductionmentioning
confidence: 99%
“…Future directions for this work could tune and slow the release rate of DOX from the NPs by increasing the polymer concentration during synthesis and then examine how release kinetics impact therapeutic efficacy. Papers have shown that by using PLGA at a concentration of 25 mg/mL, instead of the 2 mg/mL used in this work, the release of DOX from the NP can be extended over 14 days . Our NPs exhibit rapid DOX release within the first 4 h of exposure to physiological conditions (Figure ).…”
Section: Discussionmentioning
confidence: 87%
“…Papers have shown that by using PLGA at a concentration of 25 mg/mL, instead of the 2 mg/mL used in this work, the release of DOX from the NP can be extended over 14 days. 55 Our NPs exhibit rapid DOX release within the first 4 h of exposure to physiological conditions (Figure 3). This is due to the phenomenon of burst release, a common concern when using loaded PLGA.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, encodings in this paper use the same encoder. Besides, both [16] and [18] do use only one encoder for recoding in the inference stage, but not perform the same consistency constraint as we do in the training stage. Distributionally-shifted image transformation.…”
Section: Related Workmentioning
confidence: 99%